2017 26th IEEE International Symposium on Robot and Human Interactive Communication (RO-MAN) 2017
DOI: 10.1109/roman.2017.8172464
|View full text |Cite
|
Sign up to set email alerts
|

Electrodermal activity: Explorations in the psychophysiology of engagement with social robots in dementia

Abstract: Abstract-The study of engagement is central to improve the quality of care and provide people with dementia with meaningful activities. Current assessment techniques of engagement for people with dementia rely exclusively on behavior observation. However, novel unobtrusive sensing technologies, capable of tracking psychological states during activities, can provide us with a deeper layer of knowledge about engagement. We compared the engagement of persons with dementia involved in two playful activities, a gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…A systematic assessment of engagement through behavior could be greatly beneficial to measure the meaningfulness and effectiveness of activities for the person with dementia and could be used as a complement to the assessment of clinical benefits. We define engagement as the psychological state of well-being, enjoyment and active involvement that is triggered by meaningful activities and causes people with dementia to be absorbed by the activity, more energetic and in a more positive mood (Perugia et al, 2017c ).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic assessment of engagement through behavior could be greatly beneficial to measure the meaningfulness and effectiveness of activities for the person with dementia and could be used as a complement to the assessment of clinical benefits. We define engagement as the psychological state of well-being, enjoyment and active involvement that is triggered by meaningful activities and causes people with dementia to be absorbed by the activity, more energetic and in a more positive mood (Perugia et al, 2017c ).…”
Section: Introductionmentioning
confidence: 99%
“…When stress stimulates the sympathetic nervous system, it also influences physiological parameters, such as muscle activity, heart rate, and pupil dilation [ 8 ]. EDA measurements have also been used to track mood changes in older people [ 9 ], assess the functional and behavioural health of people with dementia [ 10 ], investigate people with dementia's reactions to moral dilemmas [ 11 ], and compare individuals with dementia's engagement in social activities [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Greco et al 11 found statistical evidence concerning healthy patients and patients with bipolar disorder through features of EDA signals. Moreover, Perugia et al 12 discovered significant correlations between EDA signals and engagement in dementia patients.…”
Section: Introductionmentioning
confidence: 99%